Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/jqs.2819
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to establish calcite:aragonite ratios in archaeological mollusc shells

Abstract: Oxygen isotope thermometry from archaeological mollusc shells relies on preservation of the original crystal structure; in particular that metastable aragonite has not undergone recrystallization to calcite. Conventional methods for detecting recrystallization, however, require large sample sizes and extensive calibration, so that they cannot address variable shifts across sampling surfaces and in practice are rarely fully applied. Here we show that attenuated total reflectance Fourier transform infrared spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…2; F. nigripenne ), detectable in approximately a third of samples analyzed. Insufficient sample sizes precluded quantitative analysis using XRD, but the typical occurrence of aragonite ATR‐FTIR ν 2 peaks as weak shoulders on dominant calcite ν 2 peaks suggest it to be a subsidiary phase where present (Loftus et al ). XRD patterns were only obtained for calcitic samples but results were consistent with ATR‐FTIR data in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…2; F. nigripenne ), detectable in approximately a third of samples analyzed. Insufficient sample sizes precluded quantitative analysis using XRD, but the typical occurrence of aragonite ATR‐FTIR ν 2 peaks as weak shoulders on dominant calcite ν 2 peaks suggest it to be a subsidiary phase where present (Loftus et al ). XRD patterns were only obtained for calcitic samples but results were consistent with ATR‐FTIR data in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 2960.95 cm À1 and 2926.67 cm À1 belongs to methyl C-H stretching vibration in the group of COCH 3 (Majtan et al, 2007). The peaks at 1655.08 cm À1 and 1319.22 cm À1 are assigned to stretching (Loftus et al, 2015).…”
Section: Characteristics Of Adsorbentsmentioning
confidence: 97%
“…The crystals of the outer tube wall are approximately 25-30 µm in length and represent a spherulitic prismatic structure (SPHP) ( Figure 8F). Comparison to established FTIR spectra for calcite and aragonite as well as mixtures of the two forms (Loftus et al, 2015) revealed that the Fossil Hill serpulid tubes to be predominantly comprised of calcite (based on the absence of a double peak at the 711 and 700 cm −1 wavelength positions; see Supplementary Figure S2).…”
Section: Fossil Serpulid Tubesmentioning
confidence: 99%